When biology supports clinical diagnosis: review of techniques to diagnose ocular toxoplasmosis. Issue 7 (14th May 2019) - Greigert, Valentin; Di Foggia, Elsa; Filisetti, Denis; Villard, Odile; Pfaff, Alexander W; Sauer, Arnaud; Candolfi, Ermanno
Abstract : Toxoplasmosis is a common infection whose worldwide prevalence is estimated at 30%, with large disparities across the world. Among infected subjects, the prevalence of ocular toxoplasmosis (OT) is, however, limited to about 2% in Europe and 17% in South America. In France, it is estimated that about 1 000 000 patients present either active OT or subsequent chorioretinal scars. Toxoplasma gondii is the first cause of posterior uveitis worldwide, responsible for retinochoroiditis, at times associated with anterior uveitis. To date, there is no consensus yet on how to diagnose OT, which is often based only on clinical presentation. Nevertheless, OT-associated symptoms are often atypical and misleading. Over the last 20 years, tremendous progress has been made in biological tools, enabling parasitologists to confirm the diagnosis in most suspected cases of OT. Using anterior chamber puncture, a safe and fast procedure, ophthalmologists sample aqueous humour for analysis using multiple techniques in order to reach high specificity and sensitivity in OT diagnosis. In this article, we present the different techniques available for the biological diagnosis of OT, along with their characteristics, and propose a diagnostic algorithm designed to select the best of these techniques if clinical examination is not sufficient to ascertain the diagnosis.